Efektivitas Penggunaan Pupuk Anorganik Terhadap Peningkatan Produksi Benih Jagung Lamuru Di BBI Tanaman Pangan Tarus Kabupaten Kupang - Koli, Angela Marici; Joka, Umbu (MuJAgri: Musamus Journal of Agribusiness, 2023)
For the Cattle Harvesting maize Crops Program in East Nusa Tenggara, maize seeds are supplied by the Tarus Food Crops Seed Center. The effectiveness of the use of fertilizers is still a problem, especially subsidized inorganic fertilizers. The purpose of this study is to evaluate the efficacy of using inorganic fertilisers to boost the production of lamuru corn seed variants at the Tarus Food Crop Seed Center. This study used descriptive qualitative and Likert scale data analysis techniques. The Tarus Food Crop Seed Center measured the effectiveness of using inorganic fertilisers using a likert scale (4T), and the results showed that the right type and dose fell into the appropriate category, receiving a score of 3 and a percentage of 21%, while the right time and method fell into the very appropriate category, receiving a score of 4 and a percentage of 29%.